2018
DOI: 10.5603/ep.a2018.0009
|View full text |Cite
|
Sign up to set email alerts
|

Przerzut do móżdżku raka brodawkowatego tarczycy wykryty w scyntygrafii receptorów somatostatynowych

Abstract: Introduction: Distant metastases of papillary thyroid carcinoma (PTC) may lack the ability to concentrate radioiodine. In such cases, positive somatostatin receptor scintigraphy might be useful in demonstrating the expression of somatostatin receptors that are potential therapeutic targets. To date, only a few cerebellar metastases from PTC have been reported in the literature. Patient findings:We present an 82-year-old female, in whom an asymptomatic cerebellar metastasis from PTC was diagnosed by means of Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The majority of the RDMs were identified post-operatively, while they were scarcely ever identified pre-operatively. It has been shown that among 1200 thyroid carcinoma patients treated in Czepczynski R's institution, fewer than 1% had distant metastases detected at the time of the initial diagnosis (25). Of note, a literature review by Davidson M showed that almost all PTC's pancreatic metastases were post-operatively identified (26).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the RDMs were identified post-operatively, while they were scarcely ever identified pre-operatively. It has been shown that among 1200 thyroid carcinoma patients treated in Czepczynski R's institution, fewer than 1% had distant metastases detected at the time of the initial diagnosis (25). Of note, a literature review by Davidson M showed that almost all PTC's pancreatic metastases were post-operatively identified (26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of pasireotide in combination with everolimus, an mTOR inhibitor, is proposed with improved therapeutic values in selective thyroid tumours [ 456 ]. It is also worth mentioning here that SSTR scintigraphy has been used to detect cerebellar metastasis of PTC [ 457 ]. Although controversies exist, the role of SST and its analogues in thyroid tumour diagnosis and prognosis cannot be denied in a receptor and tumour-specific manner.…”
Section: Somatostatin Receptors and Thyroid Cancermentioning
confidence: 99%
“…Conversely, in the case of non-iodine avid metastases, false-negative results are observed. In these rare situations, different techniques such as 18F-FDG PET/CT or somatostatin receptor scintigraphy may be helpful [15].…”
Section: Opis Przypadkumentioning
confidence: 99%